Aleksandr Bloks „Dvěnadcatʹ“: Zur Entdeckung der verschollen geglaubten ersten Reinschrift - Seidel, Anne (Wiener Slawistischer Almanach, 2025)
The manuscript of one of the great masterpieces of twentieth century Russian literary history has reappeared: Silver Age poet Aleksandr Blok’s first preserved handwritten fair copy, initially used as “printing copy ˮ of Dvěnadcatʹ (The Twelve) for the first publication in the newspaper Znamja Truda in 1918, with the poet’s last crucial changes, has been discovered. Up until now, this manuscript was thought to be lost. Most recently it was mentioned as missing in the critical edition of Blok’s work (Blok 1999). The manuscript survived WW II in the ownership of Blok’s friend and editor Ivanov-Razumnik and contains some editorial and scholarly comments by him as well, the latter relating to his edition of Blok’s Dvěnadcatʹ (Blok 1933). The handwritten fair copy (čistovik) was acquired by the Amherst Center for Russian Culture (ACRC), Massachusetts (USA), in 2007 through a family which was related to Ivanov-Razumnik, unnoticed by scholars untill today.This article examines the genesis and provenance of the recently discovered manuscript in detail. In addition, some of Blok’s important changes therein are discussed and interpreted in comparison with earlier and later textual witnesses and authorized prints to understand more accurately how Blok worked and to show which difference the reappeared manuscript of Dvěnadcatʹ makes to our previous understanding of the poem’s genesis.